Meta-analysis of the gender outcomes in Pakistan's agricultural evaluations - Minhas, Sidra (DevTrio Consultants, 2019)
Presented by Sidra Minhas (DevTrio) on February 28, 2019, as part of the webinar 'Changing gender norms in agriculture projects - What works in Pakistan and Ethiopia'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and the CGIAR Research Program on WHEAT.